Need Analysis for Digital Comic Teaching Materials Limatara Folklore in Increasing Class 76 Students' Reading Interest Middle School LS Idoharjo - Arisandi, Desy; Charli, Leo; Sari, Inda Puspita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the need for digital comic teaching materials for Limatara folklore in an effort to increase reading interest in grade 7.6 students of SMPN 1 Sidoharjo. Generation Z, as today's students, requires learning media that suits their characteristics and learning styles. The results of the study indicate that there is a significant need for the development of teaching materials that are interesting, interactive, and relevant to the digital world. Digital comics are seen as effective media because they can be presented online via devices such as mobile phones, making them more practical and easier to access compared to printed teaching materials. By utilizing available technology, digital comics can increase students' motivation and interest in reading folklore materials, especially Limatara folklore. Therefore, the development of teaching materials in the form of digital comics is highly recommended as an innovative alternative in learning Indonesian.